Tuning sign reversed oscillatory magneto-resistance via controlling hole concentration in La0.3Pr0.4Ca0.3MnO3∕LaAlO3 thin films. (November 2018) - Alagoz, H.S.; Gajjar, K.; Chow, K.H.; Jung, J.
Abstract: The temperature and magnetic field dependent oscillatory magneto-resistance of a compressively strained La0.3 Pr0.4 Ca0.3 MnO3 thin film was measured for various post annealing conditions (i.e., Argon/Air) in order to study the effects of hole concentration on the magnitude of the negative AMR below the crossover temperature T*. It was found that Ar and Air annealing have adverse effects on the negative AMR below T*. Interestingly, annealing driven hole doping and A-site Pr doping show similar effects on the negative AMR of these films. The mechanism responsible for these changes is discussed. Highlights: We report oscillatory magneto-resistance (AMR) in compressively-strained La0.3 Pr0.4 Ca0.3 MnO3 thin films. Argon and Air annealing have an adverse effect on the negative sign of the AMR below cross-over temperatures. Electronic uniformity has a direct effect on the sign reversal below cross-over temperature. Annealing driven changes in the hole concentration and A-site doping show similar effect on the negative sign of the AMR.